Effect of sub-critical temperature during water extraction on the yield and total antioxidant properties of germinated brown rice (Journal of Basic and Applied Research in Biomedicine, 2022)
The aim of this study is to investigate the effect of temperature on the yield and total antioxidant activity of germinated brown rice variety. The brown rice was germinated, size reduced and analysed for amylose. Extraction of 25 g of the size reduced sample was done at varied sub-critical temperatures of 25°C, 100°C, 120°C, 150°C and 180°C with water for 1 h. The resulting mixtures were the filtered and evaporated to dryness. Total antioxidant activity was then evaluated using the 2, 2’-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging ability assay and the 2,2-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical cation scavenging assay. The yield of the extract was directly proportional to the extracting temperature. The extract obtained at 25°C had the lowest yield (3.15%) while that obtained at 180°C had the highest yield (61.10%). The percentage DPPH scavenging activity of the extracts and the ABTS radical cation scavenging activity of the extracts followed same pattern, they were both inversely proportional to the extracting temperature, except for the extract at 100°C which showed a slightly lower total antioxidant activity when compared to the extract at 120°C. In conclusion: Increase in temperature during extraction was directly proportional to the yield of the extracts and inversely proportional to the total antioxidant activity of the extracts.